HUBUNGAN POLA MAKAN DAN STATUS GIZI DENGAN HASIL BELAJAR BIOLOGI PESERTA DIDIK DI SMAN 2 MAKASSAR - Maulani, Novia; Taiyeb, A. Mushawwir; Rahmat Saleh, Andi (Jurnal Biogenerasi, 2024)
This study aims to determine the diet, nutritional status and learning outcomes of students at SMAN 2 Makassar and to determine the relationship between diet and nutritional status with learning outcomes of students at SMAN 2 Makassar. This research is a correlational study approach. The data were analyzed using descriptive analysis and inferential analysis in the form of regression test and multiple linear correlation test. The results of inferential analysis showed that there was a relationship between diet and nutritional status with student learning outcomes at SMAN 2 Makassar based on a significance value of 0.002 < 0.05. The evenness of the relationship is in the “low” category based on the correlation value (R) of 0.227. The contribution of diet and nutritional status with learning outcomes based on the coefficient of determination (R2) is 0.051%, while the remaining 94.9% is the contribution of several other factors.